Commuting graphs, C(G, X) in symmetric groups Sym(n) and its connectivity - Nawawi @ Mohamed Nawawi, Athirah; Said Husain, Sharifah Kartini; Kamel Ariffin, Muhammad Rezal (MDPI, 2019)
A commuting graph is a graph denoted by C(G,X) where G is any group and X, a subset of a group G, is a set of vertices for C(G,X) . Two distinct vertices, x,y∈X , will be connected by an edge if the commutativity property is satisfied or xy=yx . This study presents results for the connectivity of C(G,X) when G is a symmetric group of degree n, Sym (n) , and X is a conjugacy class of elements of order three in G.